An Analysis Of Production Cost Calculating For Determining The Selling Price Of Kue Tat Cik Jum Home Industry In Bengkulu City - Annisah Oktariani; Yun Fitriano; Yesi Indian Ariska (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
Businesses with an SME background have increased, especially in the Home Industry which is centered on traditional food, one example is Kue Tat Cik Jum. The method used is descriptive quantitative using the full costing method for calculating the production cost and determining the selling price using the full cost pricing method. The purpose of this study was to find out how the calculation for determining the production cost at the home industry Kue Tat Cik Jum of Bengkulu City. The results of this study indicate that the calculation of the production cost carried out according to Kue Tat Cik Jum in 2021 is IDR 19.832 and in 2022, it is IDR. 20,950, - therefore the profit earned in 2021 is Rp. 2.168, - per fruit and the profit earned in 2022 is Rp. 1,050, - per fruit. While the calculation of production cost of uses the full costing method in 2021 of Rp. 24.444, -, in 2022 it is Rp. Rp. 21.703, -, therefore the profit earned in 2021 is Rp. 6.056, - per fruit and in 2022 it is Rp. 6,797,- per fruit, with a profit from determining the selling price of 25%. There is a difference between the calculation of production cost of carried out Kue Tat Cik Jum and the calculation of production cost using the full costing method in 2021 the difference is IDR 2.612, and in 2022 the difference is IDR 1.753, the difference in this calculation is due to the calculations made by Kue Tat Cik Jum does not take into account factory overhead costs, such as electricity and water costs.